2021
DOI: 10.4103/ijmy.ijmy_186_21
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interferon-Gamma and Interferon-Gamma Receptor in Tuberculosis and Nontuberculous Mycobacterial Infections

Abstract: Mycobacterium tuberculosis (Mtb) and nontuberculous mycobacteria (NTM) remain the leading causes of lung disease and mortality worldwide. Interferon-gamma (IFN-γ) and its receptor (IFN-γR) play a key role in mediating immunity against Mtb and NTM. This study was conducted as a systematic review; all information was collected from databases such as: PubMed, Scopus, Medline, SID, and medical databases. Finally, all the collected data were reviewed, and all content was categorized briefly. There is growing eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The fourth phase of immune defense will be triggered by pulmonary pathogens that were not suppressed by one of the earlier phases of immune defenses. The fourth phase of immune defense will not only be triggered by viral pathogen infections; studies have demonstrated that fungal pathogen and bacterial pathogen infections will also trigger the fourth phase of immune defense [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fourth phase of immune defense will be triggered by pulmonary pathogens that were not suppressed by one of the earlier phases of immune defenses. The fourth phase of immune defense will not only be triggered by viral pathogen infections; studies have demonstrated that fungal pathogen and bacterial pathogen infections will also trigger the fourth phase of immune defense [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ also plays a critical role in host defense by activating macrophages against dangerous intracellular bacterial pathogens including Mycobacterium tuberculosis [ 39 ]. In addition, IFN-γ has been shown to be an integral part of other antibacterial actions, including granuloma formation and phagosome-lysosome fusion, both of which control intracellular Mycobacterium [ 39 ]. Therefore, the absence of IFN-γ is associated with severe diseases from intracellular bacterial pathogens including M. tuberculosis or Mycobacterium nontuberculosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interferon gamma/interleukin-12 positive feedback loop is critical for immunity against nontuberculous mycobacterium and mycobacterium tuberculosis. 1 The use of IFN-γ as an effective treatment for these infections has been poorly described, particularly in the pediatric population. Diniz et al 2 and Alangari et al 3 describe cases of individuals with an underlying impairment in the interferon gamma/interleukin-12 receptor pathway with nontuberculous mycobacterial infections that were responsive to IFN- γ as an adjunctive treatment to their regimen.…”
Section: To the Editorsmentioning
confidence: 99%
“…Although IFN-γ production from NK and NKT cells as well as CD4 + and CD8 + lymphocytes play primary function on anti-Mtb immune response, macrophages are capable of producing IFN-γ and promoting of host defense mechanisms that control Mtb infection [6] . IFN-γ signaling leads to autophagy, phagosome maturation, programmed death activation of host cells, ROS generation and other mechanisms to act against Mtb [7] .…”
Section: Introductionmentioning
confidence: 99%